ZAKAT PRODUKTIF SEBAGAI MEKANISME DISTRIBUSI PENDAPATAN: ANALISIS TRANSFORMASI MUSTAHIK DAN KEBERLANJUTAN EKONOMI DALAM PERSPEKTIF EKONOMI MAKRO ISLAM - Dia Nur Avita Sari; Aulia Devi Rahmawati; Siti Musfiqoh (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
This study aims to analyze the role of productive zakat as an income distribution mechanism from the perspective of Islamic macroeconomics. The research employs a descriptive-analytical qualitative method using secondary data obtained from reports published by the National Zakat Agency (BAZNAS). The findings indicate that productive zakat functions as a distribution system through the collection, distribution, and empowerment of mustahik (zakat beneficiaries). the program increases income, supports business development, and promotes economic self-reliance. The sustainability of benefits experienced by mustahik demonstrates that productive zakat contributes to a more equitable distribution of income. therefore, produtive zakat serves as an instrument for achieving economic equity within the framework of islamic economics. Keywords : Productive Zakat, Income Distribution, Economic Suistanability